2014
DOI: 10.1002/2013gc005217
|View full text |Cite
|
Sign up to set email alerts
|

Re-Os age and depositional environment for black shales from the Cambrian-Ordovician boundary, Green Point, western Newfoundland

Abstract: Chemical and isotopic signatures for black shales serve as potential proxies for reconstruction of paleoenvironmental conditions. Here we bring Rock-Eval, major and trace element and Re-Os isotopic data together to examine the environmental record at the Cambrian-Ordovician Global Stratotype Section and Point (GSSP) at Green Point in western Newfoundland, Canada. The Green Point shales are oil mature and contain Type II organic material of marine origin. A Re-Os isochron for the shales provides the first radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 85 publications
(150 reference statements)
1
15
0
Order By: Relevance
“…Under highly reducing conditions, Re may be more readily incorporated into organic-rich material (Yamashita et al, 2007). The shale parting near the Matewan-Betsie contact is marked by high sulfur content (28 wt.%) and Re is enriched relative to Os in the presence of highly sulfidic waters (Helz and Dolor, 2012;Tripathy et al, 2014). Molybdenum, which is geochemically similar to Re, is effectively precipitated under euxinic conditions by conversion to thiomolybdates (Helz et al, 1996), which may also contribute to the enriched Re values observed in the Betsie.…”
Section: Re-os Fractionation In the Betsie Shale Membermentioning
confidence: 99%
See 1 more Smart Citation
“…Under highly reducing conditions, Re may be more readily incorporated into organic-rich material (Yamashita et al, 2007). The shale parting near the Matewan-Betsie contact is marked by high sulfur content (28 wt.%) and Re is enriched relative to Os in the presence of highly sulfidic waters (Helz and Dolor, 2012;Tripathy et al, 2014). Molybdenum, which is geochemically similar to Re, is effectively precipitated under euxinic conditions by conversion to thiomolybdates (Helz et al, 1996), which may also contribute to the enriched Re values observed in the Betsie.…”
Section: Re-os Fractionation In the Betsie Shale Membermentioning
confidence: 99%
“…155 Ma (Cohen et al, 1999) to ca. 2695 Ma and provide dates that refine the geologic time scale (Tripathy et al, 2014;Xu et al, 2009Xu et al, , 2014. Although not strictly for use in marine deposits (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Re-Os isotopic analyses of the samples were carried out following established analytical methods for shale at the AIRIE (Center for Applied Isotope Research for Industry and Environment) Program, Colorado State University (Yang et al, 2009;Georgiev et al, 2011;Tripathy et al, 2014) Selby and Creaser, 2003). Osmium from this solution was purified following a combination of solvent (CCl 4 ) extraction and microdistillation methods, whereas pure Re was extracted using conventional chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Re and Os in reducing sediments have a strong association with organic matter and sulfides, and are mostly hydrogenous. Given the long half-life of 187 Re (41.6 Ga) and typically high Re/Os ratios in marine sediments, the 187 Re-187 Os geochronology can provide depositional ages for marine and lacustrine organic-rich shale of widely ranging age, from Archean to Mesozoic (e.g., Selby and Creaser, 2005;Yang et al, 2009;Xu et al, 2009;Georgiev et al, 2011;Tripathy et al, 2014). A recent study of PGE (platinum group element) patterns for shale and coal samples (Baioumy et al, 2011) has established that Re and PGEs in terrestrial organic-rich sediments remain unaltered during diagenesis and the coalification processes.…”
Section: Introductionmentioning
confidence: 99%
“…The passive margin succession of the Ordovician lower boundary GSSP at Green Head, western Newfoundland (e.g., James et al, 1989;Cooper et al, 2001) is a section that requires dating by non-volcanic zircon techniques. Tripathy et al (2014) dated black shales in the boundary interval at Green Point on the basis of Re-Os ratios and their relationship to the organic maturity of associated hydrocarbons. Their proposed date of 484 ± 16 Ma falls within the range of more highly resolved U-Pb zircon dates on the boundary.…”
mentioning
confidence: 99%